Hubungan Paritas, Anemia dan Ketuban Pecah Dini dengan Kejadian Asfiksia Neonatorum pada Bayi Baru Lahir Di RSUD Cilegon Provinsi Banten - Aisyiah Aisyiah; Rosmawaty Lubis; Siti Kurnia (STIKes Persada Husada Indonesia, 2015)
Neonatal asphyxia is a condition whereupon the newborn is unable breathe spontaneously and regularly immediately after birth. Neonatal asphyxia remains a serious problem in Indonesia. The data obtained from RSUD Cilegon in 2014 showed 1,197 births, 234 newborns with neonatal asphyxia (12.31%), 59 newborns died before the age of 7 days (77.94/1000) and neonatal asphyxia stillborns as many as 20 newborns (34%). This study aims to identify the relationship between parity, anemia and premature rupture of membranes with neonatal asphyxia in newborns in RSUD Cilegon Banten Province. The study applied a study case control design, with 92 respondents as study samples. From the results, data analysis obtained P value parity = 0.002, P value anemia = 0.007, and premature rupture of membranes P value = 0.000, where all P value values <α. In conclusion there is a significant relationship between parity, anemia, and premature rupture of membranes with neonatal asphyxia in newborns in RSUD Cilegon Banten Province. It is recommended to the RSUD Cilegon decision makers to give opportunities to RSUD Cilegon officers to attend continous training on neonatal asphyxia management to newborns.